Unformatted text preview: ln  P + ( d / r )  = rt + c P + ( d / r ) = ce rt c = e c Therefore P ( t ) = ce rt − ( d / r ) If P (0) = P , then P = c − ( d / r ) and P ( t ) = [ P + ( d / r )] e rt − ( d / r ) = P e rt + ( d / r )( e rt − 1) (2.17) We know that P e rt is the interest paid on the initial deposit of P , so ( d / r )( e rt − 1) is the interest paid on the additional deposit rate, d . 3 An alternative solution method is to use the one outlined in section 2.2....
View
Full
Document
 Fall '11
 Dr.Gwartney
 Economics

Click to edit the document details